The lead and copper isotopic composition of copper ores from the Sierra Morena (Spain) - Klein, S.; Domergue, C.; Lahaye, Y.; Brey, G.P.; Von Kaenel, H.-m. (Journal of Iberian Geology, 2009)
The paper presents lead and copper isotope analyses of 51 copper ore samples from the Sierra Morena, South of Spain. They are from ancient mines of the Iberian Peninsula collected by Claude Domergue during various field campaigns in the central Sierra Morena from 1965 to 1975. Most samples consist of copper oxide minerals such as malachite, azurite and chrysocolla and stem from the surficial sections of the ore deposits. The aim of the study was to supplement the existing reference data bank on lead isotopic compositions of ancient copper mines from the Iberian Peninsula. This is particularly important for the Sierra Morena for which data exist mostly for lead-zinc but not for copper ores. The lead isotope ratios range from 18.165 to 19.712 (206Pb/204Pb), 0.797 to 0.859 (207Pb/206Pb) and 1.955 to 2.108 (208Pb/206Pb). Two separate fields can be distinguished with a major field intermediate between the ore deposits from SW and SE Spain and a second at higher 208Pb/206Pb values. Copper isotopes were analysed additionally to provide further constraints for provenance studies. The copper isotope ratios δ65Cu of the copper oxide samples are mostly positive and higher on average than those of sulphide minerals. They are a potential tool to distinguish between either sulphide ore or oxide ore deposit derived artefacts.